PENGARUH METODE LATIHAN GAME SITUASION TERHADAP KEMAMPUAN SMASH PEMAIN BOLA VOLI BAHANA CLUB KECAMATAN PALUPUH KABUPATEN AGAM - Ilham Irja; Muhamad Sazeli Rifki (JURNAL STAMINA, 2019)
The research problem is the still low influence of the smash ability of volleyball players in the Bahana Club Palupuh District, Agam Regency. This study aims to determine the effect of game situation training methods on the ability of smash volleyball players Bahana Club in Palupuh District, Agam Regency. This type of research is quasi-experimental research. The population in this study were Bahana Club volleyball players in Palupuh Subdistrict, Agam Regency who participated in active volleyball sports in 20 people. The sampling technique was a purposive sampling technique, the samples used in this study were volleyball players of Bahana Club Palupuh District, Agam Regency, which numbered 12 men from aged 17 years to 25 years. Data collection was carried out by conducting a pre-test and post-test Smash ability The volleyball player Bahana Club in Palupuh District, Agam Regency used a smash ability test. Data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t-test) with a significance level α = 0.05. From the data analysis done, the results are obtained: There is an effect of the game situation training method on the smash ability of Bahana Club volleyball players in Palupuh district, Agam Regency, with the acquisition of the tested coefficient "t" that is t = 15.76> t table = 1.795.